2014
DOI: 10.2147/ijn.s71623
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antifungal effects of amphotericin B-TPGS-b-(PCL-ran-PGA) nanoparticles in vitro and in vivo

Abstract: Background Amphotericin B (AMB) is a polyene antibiotic with broad spectrum antifungal activity, but its clinical toxicities and poor solubility limit the wide application of AMB in clinical practice. Recently, new drug-loaded nanoparticles (NPs) – diblock copolymer D-α-tocopheryl polyethylene glycol 1000 succinate-b-poly(ε-caprolactone-ran-glycolide) (PLGA-TPGS) – have received special attention for their reduced toxicity, and increased effectiveness of drug has also been reported. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…AmB has been used for decades to treat common invasive fungal infections. Although AmB has high nephrotoxicity, nanoparticle formulations of AmB have been shown to have reduced toxicity compared to its monomer state (21,22). Similarly, the results of the present study revealed lower toxicity of AmB-NPs than free AmB, including the hemolytic activity of red blood cells and the activity of macrophages (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…AmB has been used for decades to treat common invasive fungal infections. Although AmB has high nephrotoxicity, nanoparticle formulations of AmB have been shown to have reduced toxicity compared to its monomer state (21,22). Similarly, the results of the present study revealed lower toxicity of AmB-NPs than free AmB, including the hemolytic activity of red blood cells and the activity of macrophages (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Using nano technology could possibly change the properties of the substances. Zeta potential is an important criterion for the stability of a colloidal system, and a minimum ZP of ± 20 reported by different studies is desirable (16,17). Cholesterol was used to improve stability because cholesterol can increase zeta potential (18).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo therapeutic efficacy of the prepared nanoparticles was tested by a described method [21]. Sixty 20–22-g BALB/c mice (6–8 weeks old) were infected by inhalation with a volume of 20 μL of PBS containing 5.0 × 10 5 contagious C. albicans cells.…”
Section: Methodsmentioning
confidence: 99%